2021
DOI: 10.3389/fbioe.2021.648704
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Electrochemical Sensor-Based Fe2O3@MWCNTs for Ivabradine Drug Determination in Pharmaceutical Formulation, Serum, and Urine Samples

Abstract: Ivabradine hydrochloride (IVR) is a medically important drug because of its ability to lower the heart rate. Techniques reported for IVR determination were expensive, laborious, besides being of poor selectivity. In this study, iron oxide @ carbon nanotube (Fe2O3@MWCNTs) nanocomposite and molecularly imprinted polymer (MIP) were synthesized and used in the fabrication of carbon paste electrodes (CPEs) for the potentiometric detection of IVR in biological and pharmaceutical samples. CPEs of the best sensor were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 66 publications
(92 reference statements)
1
24
0
1
Order By: Relevance
“…Carbon, metals and metal oxide nanomaterials have been used to improve the military's ability to detect biological agents. By using nanotechnology, the military would be able to create sensor systems that could detect biological agents and drugs with high sensitivity and low detection limits [55][56][57][58][59]. In the polymer manufacturing industry, nanoparticles and nanostructured materials are exploited as reinforced materials [60], e.g., and tire fillers (to increase road adhesion), in the car body (to increase rigidity), and as transparent layers in heat-insulating, moisture-free, and frost-free car windows [61].…”
Section: Contemporary Nanomaterials In Materials Engineering Applicat...mentioning
confidence: 99%
“…Carbon, metals and metal oxide nanomaterials have been used to improve the military's ability to detect biological agents. By using nanotechnology, the military would be able to create sensor systems that could detect biological agents and drugs with high sensitivity and low detection limits [55][56][57][58][59]. In the polymer manufacturing industry, nanoparticles and nanostructured materials are exploited as reinforced materials [60], e.g., and tire fillers (to increase road adhesion), in the car body (to increase rigidity), and as transparent layers in heat-insulating, moisture-free, and frost-free car windows [61].…”
Section: Contemporary Nanomaterials In Materials Engineering Applicat...mentioning
confidence: 99%
“…Bakker et al 15 reported that existence of higher amount of ionophore in case of optodes will improve the selectivity; the wt% in case of miptode 2 in this work, MIP-based ion selective electrode 11 and CX-based ion selective electrode 12 are 6%, 3% and 1%, respectively. Also, Bakker compared the selectivity coefficients for ISEs and optodes with the same amount of ionophore and ion-exchanger, which showed improved of the selectivity coefficient by and order of magnitude at exchanger amount of 10.0 mmol Kg −1 ; in this work ion-exchanger is added with amount of 13.4 mmol Kg −1 in comparison to absence of ion-exchanger in previous work, which resulted in the improved selectivity coefficients by values of 2–4 orders of magnitude, especially in case of neutral and divalent interfering species.…”
Section: Resultsmentioning
confidence: 53%
“…Six carbon paste electrodes (CPEs, sensors 6–11) were constructed using different amounts of conductive carbonaceous materials (Gr, GO, rGO, MWCNTs), plasticizer (TCP or DOP), St-STFPB ion-exchanger, LF-TPB ion-pair ( Figure 2 ), as previously reported [ 41 , 42 ]. The components of 0.3 g total weight were weighed, mixed for 20 min, and dispersed in the least amount of acetone in an agate mortar, and mixed continually by the pestle to ensure paste homogeneity, Table 1 .…”
Section: Methodsmentioning
confidence: 99%